Caracterização do vento e estimativa do potencial eólico para a região de tabuleiros costeiros (Pilar, Alagoas) - Silva, Juliane Kayse Albuquerque da (2007)
The aim of this study was to characterize the wind behavior (velocity, direction, turbulence index and gust factor), as well as a preliminary estimate of the aeolian potential in coastal region close to Maceió. The wind data utilized was collected during the MICROMA project (Micrometeorologia da Mata Atlântica Alagoana) installed at Vilanova Farm, Pilar Alagoas State (9º36 12 S, 35º53 46 W, 170 m), from July/1996 to September/1999. The results showed that the local wind is influenced by micro and macro scale phenomenon. The wind velocity (8,29m height) decreases in the winter and increases in the summer. In the two seasons the wind velocity is faster during daytime. Almost in a half of the case (46%) the wind velocity is between zero and 2,0 m.s-1. The wind direction showed a little variability and the predominant flow is from ocean to continent felt (66%). The behavior of the atmospheric turbulence is inverse to the wind velocity. The wind velocity (estimated to 75m height) in 99,5% of the cases was superior to the initial velocity to start the aero generator (2,5 m.s-1). The simulated average wind power potential value was 110,27±106,51 W.m-2.